Grandmothers’ mental health is associated with grandchildren’s emotional and behavioral development: A three-generation prospective study in Brazil - Pearson, R; Culpin, I; Loret De Mola, C; Matijasevich, A; Santos, I; Horta, B; Barros, F; Stein, A (BioMed Central, 2019)
BACKGROUND:Maternal mental health is associated with an increased risk of emotional and behavioural problems in children, and the risk is partly explained by the negative impact of maternal depression on caregiving. The role of mental health in other family members, who in many contexts also provide substantial caregiving, has received far less attention. We examined the impact of grandmothers' emotional symptoms, whose role in child care is increasing across the world, on internalizing and externalizing symptoms in grandchildren from a three-generation birth cohort study. METHODS:Prospective data from three generations in two birth cohorts 22 years apart (1982 and 2004) in Pelotas, Brazil, were used (n = 92). Mental health in grandmothers and parents was assessed using the Self-Reported Questionnaire (SRQ-20). Grandchildren were members of the 2004 birth cohort, and behavioural and emotional problems were measured using the Child-Behaviour Checklist (CBCL) at age 4 years. RESULTS:Grandmothers' symptoms were associated with more emotional and behavioural problems in grandchildren after adjustment for confounding factors. The size of the associations between grandmothers' and grandchildren mental health symptoms was comparable to the associations between maternal emotional symptoms and children emotional and behavioural problems. There was no evidence for associations with paternal symptoms. These effects were substantially stronger for maternal compared to paternal grandmothers. CONCLUSIONS:In some contexts, grandmothers' mental health may be as important to grandchild emotional and behavioural development as maternal mental health. Interventions to improve the mental health of grandmothers, as well as parents, may be important to child mental health.